Construção e validação de um instrumento para analisar o conhecimento, atitude e prática dos profissionais de saúde sobre a infecção da tuberculose no Brasil - Araujo, Renato Borges de (2023)
Brazil ranks among the 30 nations most affected by Tuberculosis (TB), despite the efforts undertaken by the National Tuberculosis Control Program. From 2018 to 2021, the IL-TB system recorded 76,507 individuals undergoing treatment for Tuberculosis infection (ITB), of which 27,369 were still in treatment, 604 were in the transfer phase, and 49,947 had successfully completed the treatment. Therefore, studying ITB plays an essential role in understanding TB epidemiology and in developing effective control strategies. To achieve this, the use of robust methodological approaches to assess the Knowledge, Attitude, and Practice (KAP) of healthcare professionals regarding the disease is necessary. In this regard, the use of validated instruments is of utmost importance. Objective: Construct and validate an instrument to Analyze the Knowledge, Attitude, and Practice of healthcare professionals in dealing with ITB in Brazil. Method: This is a methodological study in which a KAP survey was constructed and validated for content through the Delphi technique. Data collection took place between July and September 2023. Validations were conducted by 11 experts who were members of the Brazilian tuberculosis network, operating at various levels of TB care. Data were analyzed using the Content Validity Index after being tabulated and organized in Microsoft Excel 2016 spreadsheets. Results: A questionnaire with fifty-three questions was developed, divided as follows: thirteen questions on sociodemographic information, sixteen on knowledge, fifteen on attitude, and nine on practice. All questions achieved a Content Validity Index (CVI) > 0.78 after expert evaluation. Conclusion: It was possible to construct a KAP questionnaire with evidence of content validation, which can be used to assess the Knowledge, Attitude, and Practice of healthcare professionals in addressing ITB in Brazil. Subsequent results may significantly support and inform policy discussions, revealing important information about TB description and encouraging engagement across sectors to achieve the goals outlined in the strategy for TB elimination.